Surgical Management of Brain Metastases in the Perirolandic Region - Zuo, Fuxing; Hu, Ke; Kong, Jianxin; Zhang, Ye; Wan, Jinghai (Frontiers in Oncology, 2020)
Brain metastases (BM) are the most frequent intracranial tumors, which may result in significant morbidity and mortality when the lesions involve the perirolandic region. Surgical intervention for BM in the perirolandic region is still under discussion even though prompt relief of mass effect and avoidance of necrosis together with brain edema may not be achieved by radiotherapy. More recently, several researchers attempt to evaluate the benefit of surgery for BM within this pivotal sensorimotor area. Nevertheless, data are sparse and optimal treatment paradigm is not yet widely described. Since the advance in intraoperative neuroimaging and neurophysiology, resection of BM in the perirolandic region has been proven to be safe and efficacious, sparing this eloquent area while retaining reasonably low morbidity rates. Although management of BM becomes much more tailored and multimodal, surgery remains the cornerstone and principles of resection as well as indications for surgery should be well defined. This is the first review concerning the characteristics of BM involving the perirolandic region and the current impact of surgical therapy for the lesions. Future perspectives of advanced neurosurgical techniques are also presented.